The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3389/fnins.2023.1097002
|View full text |Cite
|
Sign up to set email alerts
|

Hotspots and trends in fNIRS disease research: A bibliometric analysis

Abstract: ObjectiveTo summarize the general information and hotspots of functional near-infrared spectroscopy (fNIRS)-based clinical disease research over the past 10 years and provide some references for future research.MethodsThe related literature published between 1 January 2011 and 31 January 2022 was retrieved from the Web of Science core database (WoS). Bibliometric visualization analysis of countries/regions, institutions, authors, journals, keywords and references were conducted by using CiteSpace 6.1.R3.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 66 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…Xiangyin Ye et al revealed the overview, hot spots and trends of fNIRS-based clinical disease research from 2011 to 2022; they found that cutting-edge topics include executive function, functional connectivity, Alzheimer’s disease, gait research, etc. ( 42 ). And our focus of this research is primarily on analyzing the 100 highly cited articles to identify the authors, institutions, nations, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Xiangyin Ye et al revealed the overview, hot spots and trends of fNIRS-based clinical disease research from 2011 to 2022; they found that cutting-edge topics include executive function, functional connectivity, Alzheimer’s disease, gait research, etc. ( 42 ). And our focus of this research is primarily on analyzing the 100 highly cited articles to identify the authors, institutions, nations, etc.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to renaming of some journal, we have used the original journal name in the Results section and reported the IF for 2023. (42). And our focus of this research is primarily on analyzing the 100 highly cited articles to identify the authors, institutions, nations, etc.…”
Section: Fundingmentioning
confidence: 99%
“…The innovation of fMRI made it possible to provide neurofeedback information from a more locally specific brain region of interest (ROI) [10]. Since its introduction, research has primarily focused on further developing the fMRI neurofeedback method, which ultimately led to this technique now being used in first clinical trials with the aim of demonstrating its effectiveness for patient populations [11][12][13][14][15]. However, the inherent limitations of fMRI, particularly its significant cost, overall complexity, and immobility, represent significant barriers to widespread application of fMRI neurofeedback and reduce the prospects for its future integration into routine clinical practice.…”
Section: Fnirs Neurofeedback: a Promising But Challenging Neuromodula...mentioning
confidence: 99%
“…Further investigation of this aspect could be crucial, especially in the clinical context where the early identification of cognitive deficits could be crucial for the realization of appropriate and timely interventions. In addition, clinicians should consider auditory cues and hearing loss in balance and fall-risk assessments to design tailored rehabilitation strategies, In the last 20 years, functional Near-InfraRed Spectroscopy (fNIRS) opened new fields of real-world neuroscience ( Vidal-Rosas et al, 2023 ): fNIRS has been extensively applied in cognitive neuroscience in disease research ( Ye et al, 2023 ) and in the field of gait and posture ( Menant et al, 2020 ), considering its low susceptibility to motion artifacts ( Stuart et al, 2018 ; Quaresima and Ferrari, 2019 ; Bishnoi et al, 2021 ; Yücel et al, 2021 ) and reliability ( Stuart et al, 2019 ; Ayaz et al, 2022 ). fNIRS is a non-invasive vascular-based technique that enables real-time detection of concentration changes in oxygenated (O 2 Hb) and deoxygenated (HHb) hemoglobin of the cerebral microcirculation blood vessels.…”
Section: Introductionmentioning
confidence: 99%